2016
DOI: 10.1186/s13019-016-0462-7
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy after the operation for catamenial pneumothorax – is it always necessary?

Abstract: BackgroundOur recent clinical observations put into question the routine hormonal therapy for pneumothorax recurrence prevention, in patients operated for catamenial pneumothorax (CP).MethodsRetrospective review of the treatment of four women operated for CP in a recent 32-months period.ResultsThe four presented patients with CP represent 4.8 % of the overall number of patients operated for spontaneous pneumothorax and 19 % of women operated for pneumothorax in the same period. In all patients, typical multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…Twenty-four English articles were selected during the first screening, and 13 articles in English were selected as references for this CQ in the second screening. Among these 13 articles, 11 were on catamenial pneumothorax, [58][59][60][61][62][63][64][65][66][67][68] 1 was on catamenial hemoptysis 69 and another described both conditions. 70 One was a multicenter study investigating catamenial hemoptysis, 70 10 studies were reports of single-center case studies of thoracic endometriosis, [58][59][60][61][62][63][64][65][66]70 and 2 were reviews of previous articles on catamenial pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four English articles were selected during the first screening, and 13 articles in English were selected as references for this CQ in the second screening. Among these 13 articles, 11 were on catamenial pneumothorax, [58][59][60][61][62][63][64][65][66][67][68] 1 was on catamenial hemoptysis 69 and another described both conditions. 70 One was a multicenter study investigating catamenial hemoptysis, 70 10 studies were reports of single-center case studies of thoracic endometriosis, [58][59][60][61][62][63][64][65][66]70 and 2 were reviews of previous articles on catamenial pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative recurrence rates have varied in former reports. Subotic et al (7) reported no recurrent cases. Attaran et al reported only recurrent case in 12 operated cases (14).…”
Section: Discussionmentioning
confidence: 91%
“…It was first reported in 1958 by Maurer et al (1). This unique entity of spontaneous recurring pneumothorax in reproductive women has been investigated for the past seven decades (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Recent attempts have been made to classify thoracic endometriosis-related pneumothorax as catamenial and no-catamenial thoracic endometriosis-University Hospital between March 2003 and November 2016 was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The necessity for postoperative medical therapy is defined by the gynecologist, and must be individually tailored taking to account patient age, severity of symptoms (pelvic or thoracic), and the desire for pregnancy ( 17 ).…”
Section: Discussionmentioning
confidence: 99%